Cellulose Gel Mechanoreceptors – Principles, Applications and Prospects. (20th February 2023) - Shen, Xiaoping; Zhao, Dawei; Xie, Yanjun; Wang, Qingwen; Shamshina, Julia L.; Rogers, Robin D.; Sun, Qingfeng
Abstract: In order to effectively harness varieties of mechanical waves or vibrations for the purpose of monitoring and/or powering, developments in responsive materials and conversion technologies are taking place driven by the world's current and future demands. One of the most popular novelties of the last two decades is represented by hydrogel‐ or ionogel‐based flexible iontronics which constitute a wide family of innovative smart (self‐powered) mechanoreceptors relevant for various applications such as personal health care, identity and safety monitoring, intelligent human‐machine operation interfaces, underwater listening and communication, and so on. Cellulosic gels (CGs), as a promising green substitute for fossil fuel‐derived materials, are extensively studied due to the possibility to choose between different cellulose types and to formulate networks chemically or physically, according to the adaptability requirements for each target application. The aim of this review is to showcase the cellulose structural versatility and to provide a summary of the principles during the formulation of CGs used for mechanosensing and mechanical energy scavenging, as well as their practical applications. Such an outlook of current challenges and overall prospects will serve as a stimulus for research on CG‐based mechanoreceptors in the future. Abstract : The latest progress in advanced cellulose gel (CG) mechanoreceptor iontronics is reviewed. Challenges in this area lie in the demand for property regulation principles and higher‐performance devices applied as smart ionic skin, human‐machine interfaces, monitoring systems for personal identity, security and health, and underwater systems for physiological detection, communication and listening, etc.